Gynura procumbens causes vasodilation by inhibiting angiotensin II and enhancing bradykinin actions - Lam, S.K.; Poh, T.F.; Ng, H.K.; Hoe, S.Z. (Lippincott, Williams & Wilkins, 2013)
Previous studies showed that Gynura procumbens reduced blood pressure by blocking calcium channels and inhibiting the angiotensin-converting enzyme activity. The present experiments were to further explore the effects and mechanisms of a purer aqueous fraction (FA-I) of G. procumbens on angiotensin I (Ang I)–induced and angiotensin II (Ang II)–induced contraction of aortic rings and also on the bradykinin (BK) effect on cardiovascular system. Rat aortic rings suspended in organ chambers were used to investigate the vascular reactivity of FA-I. Effect of FA-I on BK was studied by in vitro and in vivo methods. Results show that FA-I significantly (P < 0.05) decreased the contraction evoked by Ang I and Ang II. In the presence of indomethacin (10 µM) or N-nitro-L-arginine methyl ester (0.1 µM), the inhibitory effect of FA-I on Ang II–induced contraction of aortic rings was reduced. Besides, FA-I potentiated the vasorelaxant effect and enhanced the blood pressure–lowering effect of BK. In conclusion, FA-I reduced the contraction evoked by Ang II probably via the endothelium-dependent pathways, which involve activation of the release of nitric oxide and prostaglandins. The inhibition of angiotensin-converting enzyme activity by FA-I may contribute to the potentiation of the effects of BK on cardiovascular system.